Setting up model farms as farmer learning centres in Mukono and Wakiso districts, Uganda - Nsadha, Zachary; Oba, Peter; Hasahya, Emma; Dione, Michel M.; Ahumuza, Ronnie; Ouma, Emily A. (International Livestock Research Institute, 2024)
The CGIAR started a series of initiatives to implement its 2030 research and innovation strategy. One of these initiatives is the “Sustainable Animal Productivity for Livelihoods, Nutrition and Gender Inclusion” (SAPLING) an initiative implemented by the International Livestock Research Institute (ILRI), the International Centre for Agricultural Research in the Dry Areas (ICARDA) and the Alliance of Bioversity International & International Centre for Tropical Agriculture (ABC-CIAT). The aim of SAPLING is to enable 800,000 livestock producers – especially women and youth in seven countries to engage in inclusive value chains and achieve sustainable productivity gains resulting in improved livelihoods. Uganda is one of seven countries identified as a focus country for this Initiative given the importance of livestock in the livelihoods of its people and the commitment of public and private actors to transform food systems through sustainable livestock development. In Uganda, SAPLING aims to improve livelihoods of livestock producers and other actors in the pig, dairy and beef value chains.